Two-dimensional layered membrane with ultrahigh monovalent / multivalent cation selectivity as well as preparation method and application of two-dimensional layered membrane

By grafting amino groups and introducing carboxyl groups on the graphene oxide layered film, forming coordination bonds with high-valent cations, the problem of insufficient selectivity of existing membranes is solved, and the selective separation of ultra-high monovalent/multivalent cations is achieved , the selectivity is greater than 10,000, which significantly improves the separation performance of the membrane.

CN119191470AActive Publication Date: 2024-12-27XIAMEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411305935.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

The existing two-dimensional layered membranes have limited performance in monovalent/multivalent cation selectivity, with the highest selectivity of only about 100, making it difficult to meet the demand for efficient ion separation in seawater, salt lakes or wastewater.

Method used

By performing surface modification on the graphene oxide layered film, grafting amino groups and introducing carboxy groups to form coordination bonds with high-valent cations, the coupling of charge and size effects is used to prepare ultra-high monovalent/multivalent cation selectivity two-dimensional layered film. The specific steps include forming an O-acyl isourea intermediate on the graphene oxide nanosheet, then reacting with polyethyleneimine to form an amide bond, and forming a highly selective film by polyacrylic acid modification.

Benefits of technology

Achieve ultra-high selectivity of monovalent/multivalent cations, with a selectivity of up to 10,000, significantly improving the separation performance of the membrane, and effectively separating cations such as K+, Na+, Mg2+, Fe3+, Mn2+ and Al3+, with better performance than existing membranes Materials are two orders of magnitude.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191470A_ABST
    Figure CN119191470A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional layered membrane with ultrahigh monovalent / multivalent cation selectivity and a preparation method and application thereof, the two-dimensional layered membrane is a membrane formed by stacking modified graphene oxide, and the inner wall of a channel in the membrane is grafted with amino (-NH2); the surface of the membrane is modified with carboxyl groups (-COOH) and coordinated with high-valence cations. The membranes of the present invention have ultra-high selectivity to monovalent / multivalent cations.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ion transport, and in particular relates to a method for preparing a two-dimensional layered membrane for ultra-high monovalent / multivalent cation selective separation and rapid monovalent cation transport. Background Art

[0002] The development of artificial membranes for rapid and selective ion transport is very important for modern separation technology and has attracted extensive attention in the fields of lithium extraction from salt lakes, chlor-alkali industry and heavy metal ion removal. Two-dimensional nanomaterials have the advantages of single atomic layer thickness, large aspect ratio, good mechanical properties and easy film formation, making them an ideal separation membrane material.

[0003] Two-dimensional layered films are two-dimensional nanosheets assembled layer by layer by vacuum filtration, spin coating, drop coating, etc. In 2012, Nair et al. first discovered the ultrafast transport of water molecules in the interlayer channels of graphene oxide (GO) membranes, which provided a research basis for the rapid transport of ions in two-dimensional layered membranes [1]. After more than ten years of development, the types of two-dimensional layered materials used for ion separation have been greatly expanded. After studying the ion separation performance of two-dimensional layered membranes composed of many different types of materials, it was found that the selective transport of different ions in such membranes mainly comes from the interaction between ions and the size of the interlayer channels. For this reason, people have developed strategies such as ion intercalation, molecular cross-linking, and partial reduction to regulate the size effect of the channel. Despite this, the highest monovalent / divalent ion selectivity obtained so far is only about 100.

[0004] [1]Nair RR, Wu HA, Jayaram PN, Grigorieva IV, Geim AKUNimpededpermeation of water through helium-leak-tight graphene-based membranes[J].Science,2012,335(6067):442-444. Summary of the invention

[0005] The purpose of the present invention is to prepare a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity based on the basic strategy of surface modification, by controllably coupling the size effect and the charge effect, and modifying the nanosheet material with suitable functional groups. The membrane can be applied to the fields of ion separation in seawater, salt lakes or wastewater.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity, wherein the two-dimensional layered membrane is a membrane formed by stacking graphene oxide, wherein the inner wall of the channel in the membrane is grafted with amino groups (-NH 2 ); The surface of the membrane is modified with carboxyl groups (-COOH), and high-valent cations are used to form coordination bonds with the carboxyl groups, so that the high-valent cations act as gates to promote the separation selectivity of the membrane for monovalent / high-valent cations.

[0008] Another object of the present invention is to provide an application of the two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity in the selective separation of multivalent cations. The ultra-high monovalent / multivalent cation selectivity of the present invention has a maximum selectivity greater than 10,000.

[0009] In the present invention, the two-dimensional layered film is preferably a film formed by stacking graphene oxide.

[0010] In the present invention, the monovalent / polyvalent cations include K + 、Na + Mg 2+ , Fe 3+ , Mn 2+ and Al 3+ At least one of .

[0011] Another object of the present invention is to provide a method for preparing a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity, comprising the following steps:

[0012] Step 1: Disperse graphene oxide in deionized water, then add EDC and stir; EDC and the carboxyl groups on the GO nanosheets form an O-acylisourea intermediate that can react with the amino group; then add polyethyleneimine (PEI) to the mixed solution and stir, the O-acylisourea intermediate forms an amide bond with PEI, and the isourea product is released at the same time; then, the mixed solution is stirred and dialyzed in a dialysis bag until the pH of the solution is neutral; the dialyzed solution is centrifuged to obtain a positively charged PGO nanosheet slurry;

[0013] Step 2, stacking the positively charged PGO nanosheet slurry obtained in step 1 in the base film to form a PGO film, and drying to obtain a dried PGO film, the thickness of the film is 0.5 μm to 4 μm;

[0014] Step 3: Immerse the dried PGO membrane obtained in step 2 in a polyacrylic acid (PAA) solution to obtain a PGO-PAA membrane, wherein the PGO-PAA membrane is a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity.

[0015] Step 4: The PGO-PAA membrane is brought into contact with a solution containing high-valent cations, so that the high-valent cations form coordination bonds with the carboxyl groups, thereby obtaining a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity.

[0016] In a preferred embodiment, in step 1, the concentration of GO solution dispersed in deionized water is (30-70) mg / 150 ml, and the volume ratio of EDC to GO solution is 1:(200-400).

[0017] In a preferred embodiment, in step 1, the mass ratio of GO to polyethyleneimine is (30-70):1000.

[0018] In a preferred embodiment, in step 1, the molecular weight of polyimide is 400-12000.

[0019] In a preferred embodiment, in step 1, the cut-off size of the dialysis bag is 8000-14000.

[0020] In a preferred embodiment, in step 2, the thickness of the PGO film is 0.5 μm to 4 μm.

[0021] In a preferred embodiment, in step 2, a polyethersulfone (PES) microporous filter membrane is used as the base membrane.

[0022] In a preferred embodiment, the average pore size of the polyethersulfone (PES) microporous filter membrane is 0.2 μm to 0.3 μm, and the porosity is 40% to 60%.

[0023] In a preferred embodiment, in step 3, the molecular weight of the polyacrylic acid is 2000-30000.

[0024] In a preferred embodiment, in step three, the completely dried PGO membrane in step two is immersed in a polyacrylic acid PAA solution for 3h-10h, and then the PAA-treated PGO membrane is vacuum dried at 40°C to 60°C for 3h to 10h to completely dry the membrane; it is vacuum dried at 70°C to 80°C for 1h to 3h to obtain a PGO-PAA membrane; thereafter, the PGO-PAA membrane is fully immersed in deionized water to remove excess PAA molecules on the membrane surface; finally, the PGO-PAA membrane is vacuum dried again at 40°C to 60°C for 6h to 18h to obtain a completely dried PGO-PAA membrane.

[0025] In a preferred embodiment, in step 4, after the completely dried PGO-PAA membrane of step 3 is assembled into a test cell, a solution containing high-valent cations (concentration of 0.05 mM to 0.1 M) is added to one side of the test liquid to form a coordination with the carboxyl functional groups on the membrane surface to obtain a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity.

[0026] The present invention discloses a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity, which is prepared by vacuum filtration of graphene oxide (GO) nanosheets. Firstly, in order to solve the problem that the swelling of GO membrane in solution leads to the instability of the interlayer channel structure, amino groups (-NH 2 ), using the hydrogen bonding interaction between amino groups and water molecules to improve its long-term stability in salt solutions, strong acids and strong bases. Furthermore, by measuring the ion transport behavior in GO membranes with stable interlayer structures, rapid monovalent ion transport and significant trivalent cation interception were found, with the selectivity between monovalent / trivalent cations greater than 4000. Finally, by modifying the carboxyl group (-COOH) that specifically interacts with aluminum ions at the channel entrance and using "high-valent cation gating such as aluminum ions", the channel surface charge density was dynamically regulated. The maximum monovalent / divalent cation selectivity in the final film can be greater than 10,000, which is two orders of magnitude higher than the existing optimal film performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0028] Figure 1 (a) Schematic diagram of the preparation process of PGO nanosheets (b) AFM morphology and height image of PGO nanosheets.

[0029] Figure 2 (a) Optical photo of PGO membrane with PES filter substrate (b) Cross-sectional SEM image of PGO membrane (c) K of PGO membrane at different thicknesses + / Mg 2+ and K + / Al 3+ (d) Long-term stability test of PGO membrane, K + and Al 3+ The permeation rate as a function of the test time (the inset is a photo of the PGO membrane at 0 and 201 days of testing).

[0030] Figure 3 (a) Schematic diagram of the structure of PGO-PAA membrane (b) Zeta potential of PGO-PAA membrane measured in Al3+ solutions with different concentrations (the blue dashed line represents the Zeta potential of PGO-PAA membrane in the absence of Al3+, and the inset is a schematic diagram of the charge reversal on the membrane surface) (c) K + / Mg 2+ Selectivity and Al 3+ The function of concentration (d) is used to continuously measure Al in high concentration mixed salt solutions. 3+ Stability results of gated PGO-PAA membranes (e) Different metal ions in Fe 3+Selectivity of gated PGO-PAA membranes (f) Different metal ions in Mn 2+ Selectivity in gated PGO-PAA membranes.

[0031] Figure 4 (a) Different cations in Al 3+ Ion transport properties of gated PGO-PAA membranes, PEI covalently grafted with a molecular weight of 10000 (b) Different cations in Al 3+ Ion transport properties of PGO-PAA membrane treated with gated high molecular weight PAA (Mw: 250000). DETAILED DESCRIPTION

[0032] Example 1: Preparation of amino-covalently grafted graphene oxide nanosheets

[0033] Take 50 mg of GO solution and disperse it in 150 mL of deionized water for 10 minutes, then add 500 μL of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) and stir for 1 hour. In this step, EDC will react with the carboxyl groups on the GO nanosheets to form an O-acylisourea intermediate that can react with the amino group. Then, add 1 g of polyethyleneimine to the mixed solution and stir for 3 hours. The intermediate of O-acylisourea forms an amide bond with PEI and releases the isourea product at the same time. Subsequently, the mixed solution is stirred and dialyzed in a dialysis bag (cutoff size of 8000-14000) for 3 days to remove excess EDC, PEI and other small molecules until the solution pH is neutral. The dialyzed solution is centrifuged at 8000 rpm for 10 minutes to obtain a positively charged PGO (positive-GO) nanosheet slurry. Due to the addition of PEI, the agglomeration of PGO nanosheets will occur. In order to obtain a single layer of PGO nanosheets, the PGO slurry was re-dispersed in deionized water and ultrasonically dispersed to obtain a uniform solution. Then, the obtained PGO solution was centrifuged at 6000 rpm for 10 min to remove thick PGO nanosheets and obtain a solution dispersed with a single layer of PGO nanosheets.

[0034] Example 2: Preparation and ion separation performance of amino-grafted stable graphene oxide membrane

[0035] When conducting water permeation and ion permeation experiments, in order to ensure the integrity of the PGO membrane, it is hoped that the PGO membrane will not fall off the substrate easily. Therefore, we use a hydrophilic polyethersulfone (PES) microporous filter membrane. The oxygen in polyethersulfone will have a certain hydrogen bond effect with the oxygen-containing functional groups in PGO. The PGO membrane filtered using the PES filter membrane will still not fall off the substrate after complete drying. The diameter of the PES filter membrane is 25 mm, the average pore size is 0.22 μm, and the porosity is about 50%. Take 0.5 mg of PGO solution and disperse it in deionized water and stir for 0.5 h. Add the PGO solution to the upper filter cup, turn on the vane pump to vacuum the filter bottle below the PES filter membrane. After the solution in the upper filter cup is completely filtered into the lower filter bottle, the PGO nanosheets whose size is larger than the pore size of the PES filter membrane will stack under the action of the vacuum suction to form a PGO membrane. Dry the PGO membrane in a vacuum oven at 50°C for 12 hours to obtain a completely dried PGO membrane, such as Figure 2 (a) shows. The PGO film has a + / Al 3+ and K + / Mg 2+ The relationship between selectivity and membrane thickness is as follows Figure 2 As shown in (c), the ion selectivity is the highest when the thickness is 4 μm (K + / Al 3+ >4000). At the same time, after about 200 days of testing, the K + and Al 3+ The permeation rate remains stable, and K + / Al 3+ The selectivity change is less than 10%, and the results are as follows Figure 2 (d) as shown.

[0036] Example 3: Preparation and ion separation performance of graphene oxide membrane with adjustable charge density modified by carboxyl and cation coordination

[0037] The completely dried PGO membrane was immersed in a polyacrylic acid (PAA) solution (Mw=3000) for 6 hours, and then the PAA-treated PGO membrane was vacuum dried at 50°C for 4 hours to completely dry the membrane. In order to further enhance the interaction between PAA and the PGO membrane, it was vacuum dried at 75°C for another 2 hours to obtain a PGO-PAA membrane. Afterwards, the PGO-PAA membrane was fully immersed in deionized water to remove excess PAA molecules on the membrane surface. Finally, the PGO-PAA membrane was vacuum dried at 50°C for 12 hours again to obtain a completely dried PGO-PAA membrane. Due to Al 3+ will coordinate with the carboxyl groups in the PGO-PAA membrane (e.g. Figure 3a), and will be completely intercepted during the permeation process, so it can affect the transmission of other ions by adjusting the size and charge effect of the channel. 3+ It can be used as a gating ion, such as Figure 3 As shown in (b), the charge density on the surface of the PGO-PAA membrane is dynamically regulated by changing its concentration. Figure 3 As shown in (c), with the addition of Al 3+ The PGO-PAA film has a significant effect on K + / Mg 2+ The selectivity can reach up to about 12,000, which is 2 orders of magnitude higher than the best existing membrane. For practical applications, the cyclic stability of the membrane is very important, so the stability of the PGO-PAA membrane was tested in a 2M high-concentration mixed salt solution. The results are as follows Figure 3 As shown in (d), after 15 days of testing, Li + / Mg 2+ The selectivity is still greater than 3000, far exceeding the current ion-selective membrane materials. In addition, the gating ions used to regulate the surface charge density of the membrane channel are not limited to Al 3+ , and can also be extended to Fe 3+ and Mn 2+ Ions. Use Fe 3+ and Mn 2+ When ions are coordinated with PAA, Figure 3 (e) and Figure 3 As shown in (f), K + / Mg 2+ The selectivity can reach levels of >900 and >30, respectively.

[0038] Example 4: Expandable molecular weight range of amino and carboxyl polymers for modifying graphene oxide two-dimensional membrane devices

[0039] In this example, PEI with molecular weights of 600 and 10,000 were covalently grafted onto GO to prepare PGO membranes, and then their separation selectivity for monovalent / multivalent cations was tested. Figure 4 As shown in (a), as the molecular weight of PEI increases from 600 to 10,000, the selectivity of monovalent / divalent ions decreases by about one order of magnitude. This is because as the molecular weight of PEI increases, the amino functional groups grafted onto the inner wall of the channel become more abundant, thereby being able to adsorb more PAA and Al. 3+ , thus reducing the permeation rate of monovalent ions. But at the same time, higher molecular weight PEI can increase the interlayer channel size of PGO membrane, thus reducing the Mg 2+ The charge repulsion caused Mg 2+The permeation rate increases, and eventually leads to a decrease in the monovalent / divalent cation selectivity. However, even so, the monovalent / divalent ion selectivity after the decrease is better than the currently reported film performance. For PAA, which plays a carboxyl modification role, the molecular weight is also increased from 3000 to 250000. Since PAA is modified on the surface of the PGO membrane, the increase in its molecular weight will not affect the channel size of the membrane, that is, it will not affect the monovalent / divalent cation screening performance (results are shown in Figure 4 (as shown in (b)).

[0040] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.

Claims

1. A two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity, characterized in that: The inner wall of the channel in the two-dimensional layered membrane is grafted with amino groups; the surface of the membrane is modified with carboxyl groups, and high-valent cations are used to form coordination bonds with the carboxyl groups, so that the high-valent cations play a gating role and promote the separation selectivity of the membrane for monovalent / high-valent cations.

2. A two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity according to claim 1, characterized in that: The two-dimensional layered film is a film formed by stacking graphene oxide.

3. Use of a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity according to any one of claims 1 to 2 in the selective separation of multivalent cations.

4. A method for preparing a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity, comprising the following steps: Step 1, modifying amino groups on the two-dimensional layered membrane; Step 2, modifying carboxyl groups on the two-dimensional layered membrane modified with amino groups; Step three, modifying high-valent cations on the two-dimensional layered membrane modified with amino and carboxyl groups.

5. A method for preparing a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity, comprising the following steps: Step 1: Disperse graphene oxide in deionized water, then add EDC and stir; EDC and carboxyl groups on graphene oxide nanosheets form O-acylisourea intermediates that can react with amino groups; then add polyethyleneimine to the mixed solution and stir, the O-acylisourea intermediate forms an amide bond with polyethyleneimine, and the isourea product is released at the same time; Subsequently, the mixed solution is dialyzed in a dialysis bag with stirring until the pH of the solution is neutral; the dialyzed solution is centrifuged to obtain a positively charged PGO nanosheet slurry; Step 2, stacking the positively charged PGO nanosheet slurry obtained in step 1 in the base film to form a PGO film, and drying to obtain a dried PGO film; Step 3, immersing the dried PGO membrane obtained in step 2 in a polyacrylic acid PAA solution to obtain a PGO-PAA membrane; Step 4: The PGO-PAA membrane is brought into contact with a solution containing high-valent cations, so that the high-valent cations form coordination bonds with the carboxyl groups, thereby obtaining a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity.

6. The method for preparing a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity according to claim 5, characterized in that: In step 1, the concentration of GO solution dispersed in deionized water is (30-70) mg / 150 ml, the volume ratio of EDC to GO solution is 1:(200-400), and the mass ratio of graphene oxide to polyethyleneimine is (30-70):1000.

7. The method for preparing a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity according to claim 5, characterized in that: In step 1, the molecular weight of polyacetimide is 400 to 12000.

8. The method for preparing a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity according to claim 5, characterized in that: In step 3, the molecular weight of the polyacrylic acid is 2000-30000.

9. The method for preparing a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity according to claim 5, characterized in that: In step three, the completely dried PGO membrane in step two is immersed in a polyacrylic acid PAA solution for 3h-10h, and then the PAA-treated PGO membrane is vacuum dried at 40°C to 60°C for 3h to 10h to completely dry the membrane; it is vacuum dried at 70°C to 80°C for 1h to 3h to obtain a PGO-PAA membrane; thereafter, the PGO-PAA membrane is fully immersed in deionized water to remove excess PAA molecules on the membrane surface; finally, the PGO-PAA membrane is vacuum dried again at 40°C to 60°C for 6h to 18h to obtain a completely dried PGO-PAA membrane.

10. The method for preparing a two-dimensional layered membrane with ultra-high monovalent / multivalent cation selectivity according to claim 5, characterized in that: In step 4, the high-valent cations include but are not limited to Al 3+ , Fe 2+ , Mn 2+ , the high-valent cation concentration range is 0.05mM~0.1M.

Citation Information

Patent Citations

  • Preparation method of graphene oxide and magnetic mesoporous silica composite material capable of adsorbing pollutants in water

    CN103432996A

  • Transport membrane with lithium ion selectivity and preparation method and application thereof

    CN116272409A

  • Preparation method and application of monovalent cation selective separation membrane of montmorillonite-based two-dimensional nano ion transmission channel

    CN117323841A

  • Ceramic go / PEI nanomembrane by layer-by-layer assembly based on covalent bond using EDC chemistry and method for manufacturing the same

    US20220194869A1